Vaginal Implant Transmitters as a Tool for Pronghorn Fawn Capture - Emily R. Conant; Warren C. Conway; Mark C. Wallace; Nicole M. Tatman (Wildlife Society Bulletin)
ABSTRACT During a pronghorn (Antilocapra americana) translocation study in New Mexico, USA, in 2014, we outfitted 26 pregnant female pronghorn with vaginal implant transmitters (VITs) to better understand cause‐specific fawn mortality. All VITs were equipped with both temperature and photo (i.e., light) sensors. Partial expulsions were detected from VITs in April 2014, at least 2 weeks prior to fawn observations. In these instances, VITs were exposed to ambient daylight activating the photo sensor, which was “reset” daily after sunset. These false signals likely compromised both battery life as well as detection of actual fawn births as a result of time spent tracking false expulsions rather than focusing efforts on fawn capture. We tracked VITs of 19 females (n = 16 confirmed expelled). Expelled VITs assisted with fawn captures (n = 12) from 8 females. We were unable to capture fawns from some females with VITs because fawns were too old to capture or VIT signal failure limited our ability to correctly determine whether a birth occurred. Failure here is defined as a signal we were unable to hear due either to battery failure or geographic location of the VIT post‐expulsion. We also opportunistically captured fawns, either by monitoring and observing females outfitted with very‐high‐frequency (VHF) collars or using long‐range observations of unmarked females. Opportunistic captures resulted in fawn captures (n = 4) from 3 females with only VHF collars, and 13 fawns from 13 unmarked females. Fawn capture success from females whose VIT expelled was greater because fawns were smaller and less likely to flee. To minimize false expulsion signals in VITs, we recommend 1) modification of VIT wings to maintain position inside the vaginal canal until parturition, and 2) change VIT design to specifically fit pronghorn (i.e., design VITs using specific pronghorn vaginal canal measurement to ensure better VIT fit) to prevent premature partial or total expulsion. © 2019 The Wildlife Society.